2018
DOI: 10.1175/bams-d-16-0293.1
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-Based Atmospheric Infrared Sounder Development and Applications

Abstract: A history of the meteorological satellite-based atmospheric sounder development and applications is presented and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 144 publications
(98 citation statements)
references
References 119 publications
0
98
0
Order By: Relevance
“…To improve our knowledge of atmospheric thermodynamics, an effective approach is to use radiance measurements from the high spectral infrared (IR) sounders (or the advanced IR sounders; Menzel et al, ), which provide temperature and constituent profiles at a higher accuracy and vertical resolution than the classic IR sounders such as the High‐resolution Infrared Radiation Sounder (Smith et al, ) and the Geostationary Operational Environmental Satellite (GOES) Sounder (Menzel & Purdom, ). The advanced IR sounders, such as the Atmospheric Infrared Sounder (Chahine et al, ) onboard the Earth Observing System Aqua platform, the Infrared Atmospheric Sounding Interferometer (IASI) onboard the MetOp‐A and MetOp‐B satellites (Hilton et al, ), and the Cross‐Track Infrared Sounder (CrIS) onboard Suomi National Polar‐orbiting Partnership and Joint Polar orbit Satellite System series (Goldberg et al, ), have proved that the assimilation of radiances from those sounders has a significant positive impact on global and regional numerical weather prediction (NWP; Le Marshall et al, ; J. Li et al, ; McNally et al, ; Wang et al, , , ).…”
Section: Introductionmentioning
confidence: 99%
“…To improve our knowledge of atmospheric thermodynamics, an effective approach is to use radiance measurements from the high spectral infrared (IR) sounders (or the advanced IR sounders; Menzel et al, ), which provide temperature and constituent profiles at a higher accuracy and vertical resolution than the classic IR sounders such as the High‐resolution Infrared Radiation Sounder (Smith et al, ) and the Geostationary Operational Environmental Satellite (GOES) Sounder (Menzel & Purdom, ). The advanced IR sounders, such as the Atmospheric Infrared Sounder (Chahine et al, ) onboard the Earth Observing System Aqua platform, the Infrared Atmospheric Sounding Interferometer (IASI) onboard the MetOp‐A and MetOp‐B satellites (Hilton et al, ), and the Cross‐Track Infrared Sounder (CrIS) onboard Suomi National Polar‐orbiting Partnership and Joint Polar orbit Satellite System series (Goldberg et al, ), have proved that the assimilation of radiances from those sounders has a significant positive impact on global and regional numerical weather prediction (NWP; Le Marshall et al, ; J. Li et al, ; McNally et al, ; Wang et al, , , ).…”
Section: Introductionmentioning
confidence: 99%
“…Sounding capability from geostationary satellites began in 1980 with the VISSR Atmospheric Sounder (VAS) on GOES satellites; see Smith (1991) and Menzel et al (2018) and their references. VAS continued in operation until 1996; the application and impact of the VAS data is summarised by Smith (1991).…”
Section: Early Instrumentsmentioning
confidence: 99%
“…Although the advanced sounding products that were originally envisioned for GOES-R series cannot be realized with the Hyperspectral Environmental Suite withdrawn, legacy sounding products that are used by the National Weather Service and other agencies must be provided. Schmit et al (2008) showed that adequate substitute products can be generated from ABI data in conjunction with information from short-term numerical model forecasts, although the quality would be slightly inferior to the GOES-13/GOES-14/GOES-15 Sounder performance, and significantly less capable than a highspectral resolution sounder with respect to information content and retrieval accuracy (Menzel et al, 2018;Schmit et al, 2009). ABI bands 8-16 (6.15 to 13.3 μm), which include four absorption bands (three water vapor bands and one CO 2 ), are the primary channels used in LAP retrieval.…”
Section: Goes-16 Observations Lap Algorithms and Productsmentioning
confidence: 99%